The Utilization of the Game Technique as a Test Instrument to Determine the Persistence of Applicants - Joni, Joni; Prasandy, Teguh; Murmanto, Imanuel Revelino (ULTIMA InfoSys, 2024)
This research was conducted at PT. XYZ, which utilizes the game elements in the process of psychological test. This game-based test is intended to measure the persistence of applicants (management-trainee position) and to replace Pauli Test, which is administered through a paper and pencil test method. Results of the game-based persistence test are proven to have a positive correlation with the measurement of persistence in the measurement of persistence on the Pauli Test (p-value <.05, koef. Correlation (+)). This project was developed using iOS platform from Apple, which automates the process of psychological test by applying Computer Based Test (CBT) which uses iPad media.